2017
DOI: 10.1186/s13068-017-0988-5
|View full text |Cite
|
Sign up to set email alerts
|

Production of isoprene, one of the high-density fuel precursors, from peanut hull using the high-efficient lignin-removal pretreatment method

Abstract: BackgroundIsoprene as the feedstock can be used to produce renewable energy fuels, providing an alternative to replace the rapidly depleting fossil fuels. However, traditional method for isoprene production could not meet the demands for low-energy consumption and environment-friendliness. Moreover, most of the previous studies focused on biofuel production out of lignocellulosic materials such as wood, rice straw, corn cob, while few studies concentrated on biofuel production using peanut hull (PH). As is kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The production of biohydrocarbons from LCB is a relatively underexplored field, as indicated in Table 2. Wang et al (2017) created the recombinant E. coli overexpressing MVA pathway (containing mvaE and mvaS MT from Enterococcus faecalis) and ipsS (isoprene synthase, from Papulus alba). The strain could produce 249-298 mg/L of isoprene from peanut hull hydrolysate in separate hydrolysis and fermentation, and SSF respectively (Wang et al, 2017).…”
Section: Biohydrocarbons (Isoprene and B-farnesene)mentioning
confidence: 99%
See 1 more Smart Citation
“…The production of biohydrocarbons from LCB is a relatively underexplored field, as indicated in Table 2. Wang et al (2017) created the recombinant E. coli overexpressing MVA pathway (containing mvaE and mvaS MT from Enterococcus faecalis) and ipsS (isoprene synthase, from Papulus alba). The strain could produce 249-298 mg/L of isoprene from peanut hull hydrolysate in separate hydrolysis and fermentation, and SSF respectively (Wang et al, 2017).…”
Section: Biohydrocarbons (Isoprene and B-farnesene)mentioning
confidence: 99%
“…Wang et al (2017) created the recombinant E. coli overexpressing MVA pathway (containing mvaE and mvaS MT from Enterococcus faecalis) and ipsS (isoprene synthase, from Papulus alba). The strain could produce 249-298 mg/L of isoprene from peanut hull hydrolysate in separate hydrolysis and fermentation, and SSF respectively (Wang et al, 2017). In another study, recombinant E. coli overexpressing the MEP pathway and ipsS was created and employed for the production of isoprene from paper mill sludge hydrolysate.…”
Section: Biohydrocarbons (Isoprene and B-farnesene)mentioning
confidence: 99%
“…In addition, pre-treatment leads to the release inhibitory compounds, which can greatly hinder cell viability and productivity. These include phenolic compounds (ferulic acid, p-coumaric acid), furan derivatives (furfural, 5-hydroxymethylfurfural) and small organic acids (levulinic acid, formic acid, and acetic acid) (Wang S. et al, 2017;Navarrete et al, 2020).…”
Section: Lignocellulosic Biomassmentioning
confidence: 99%
“…Some attempts have been made for the development of an economically viable process for producing isoprene by using recombinant microbial systems-mainly bacteria, yeast, and cyanobacteria [14][15][16][17]; however, the sustainable and renewable production of isoprene, using CO 2 from recombinant cyanobacteria, could be an appropriate model production system [18,19]. Studies have also shown that isoprene can be a potential alternative to petroleum-based fuels due to its high energy density and low viscosity properties [19,20]. Recently, the hydrogenated isoprene dimers (C 10 H 20 compounds-derivatives of cyclobutene, cyclohexane, and cyclooctane) from recombinant cyanobacteria have been characterized as ideal drop-in jet fuel [19,21].…”
Section: Introductionmentioning
confidence: 99%